The Gut Microbiota of Healthy Infants in the Community is a Reservoir for ESBL and Carbapenemase Producing Bacteria. (4th October 2017) - Saleem, Ali; Allana, Ahreen; Hale, Lauren; Qureshi, Shahida M; Hotwani, Aneeta; Rahman, Najeeb; Khan, Asia; Seed, Patrick; Arshad, Mehreen
Abstract: Background: The recent rapid rise of Extended-spectrum Β Lactamase producing Gram-negative bacteria (ESBL-GNB) has seriously threatened the treatment of common infectious diseases. Neonates have an immature immune system and a delay in appropriate treatment due to ESBL-GNB sepsis can be fatal. This problem of delayed therapy is magnified in the developing world where 99% of the deaths from community acquired neonatal sepsis occur. Additionally ESBL E. coli such as the strain ST131 are known to be persistent gut and vaginal colonizers. In animal models, these strains out-compete colonization with drug-sensitive, commensal E. coli . Gut colonization with ESBL-GNB in infants may therefore have a profound impact on their microbiome and increase their risk of sepsis. Pakistan is a lower middle income country with high antibiotic use per capita and a sharp increase in ESBL-GNB infections. Recent data show that >50% of E. coli isolates from reproductive-aged women of Pakistan are resistant to more than one class of antibiotics. We aimed to determine the rates of gut colonization with ESBL-GNB among healthy infants in a community setting. Methods: Stool samples were collected from 100 healthy infants living in a Pakistani suburban community between the ages of 5 and 7 months. Samples were plated on MacConkey agar to select for Gram-negative bacteria. Isolates were screened for resistance against several antimicrobial classes. Molecular testing of the stool samples was done using primers targeting conserved regions of ESBL and carbapenemase genes. Results: Forty-eight percent of the infants were positive for ESBL producing Gram-negative bacteria, the majority of which were E. coli, and 7.5% were positive for carbapenemase producers, all of which belonged to Klebsiella spp. Molecular testing showed that 85% of the infant stools were positive for TEM β-lactamase gene, 68% for the CTX-M β-lactamase gene and 33% for the KPC carbapenemase gene. Conclusion: The widespread colonization of infants in a developing country with ESBL-GNB is highly concerning. Further, our studies have revealed that the resistome of otherwise healthy infants may be a major reservoir of antibiotic genes in the community. Gut microbiome analysis of the potential impact of colonization with antibiotic-resistant bacteria is on-going. Disclosures: All authors: No reported disclosures.